ANALISIS KUALITAS PELAYANAN, SERTA PENGARUHNYA TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN (Survei Pada Pengunjung SnowBay Waterpark TMII) - Kresnamurti R. P., Agung; Sinambela, Dian Siskawati (Fakultas Ekonomi, Universitas Negeri Jakarta, 2011)
The purpose of this research are to clearly describe about service quality, customer satisfaction, and customer loyalty of SnowBay Waterpark TMII. This research used descriptive and explanatory method. Unit analysist of this research is the visitors of SnowBay Waterpark TMII that have ever visit SnowBay before and are in the age or above 17th years old. Total sampel of this research are 200 respondences. The analysis tools that are used in this research are SPSS 16.0 and SEM 8.7. The result of the descriptive analysis in this research shows: (1) tangibles become the most contribute dimension toward service quality; (2) attributes related to purchases become the most contribute dimension toward customer satisfaction; (3) advocate become the most contribute dimension toward customer loyalty. The result of hypothesis testing are: (a) service quality has positive and significant effect toward customer satisfaction, with t-value 10.76 or t-value > 2; (b) service quality does not has significant effect toward customer loyalty, with t-value 0.15 or t-value < 2; (c) customer loyalty has positive and significant effect toward customer loyalty, with t-value 5.39 or t-value > 2. Keywords: Service Quality, Customer Loyalty, Customer Satisfaction, SnowBay Waterpark TMII.